How to manifest the fertilizer reduction effect of pro-environmental agricultural technologies? From the perspective of farmers’ perception and behavioral adoption - Kuang, Foyuan; Li, Jiatong; Jin, Jianjun; Liu, Changjin; Qiu, Xin (Frontiers in Sustainable Food Systems, 2024)
Introduction The ecological and environmental pollution problem at the source of agriculture cannot be ignored, and the manifestation of the fertilizer reduction effect of pro-environmentally agricultural technologies (PEATs) will help motivate farmers to adopt technology, thereby promoting sustainable agricultural development. Methods From the dual perspectives of farmers’ perception and behavior effects, this paper uses 607 survey data of Chinese farmers, and an endogenous switching regression model is employed to identify the influencing factors of farmers’ adoption of PEATs and manifest its fertilizer reduction effect. Results and discussion The results of the perception survey show that the farmers’ recognition of the fertilizer reduction effect of PEATs is not high, and the technical effect needs to be further demonstrated. Moreover, the estimated results suggest that PEATs can significantly reduce the fertilizer application of farmers. Specifically, if farmers who have adopted PEATs do not adopt them, they will apply more chemical fertilizers, the farmers who have not adopted PEATs will use less chemical fertilizer if they do. Overall, the main influencing factors for farmers adopting PEATs include education level, government officials, cultivated land area, soil fertility, information access channels, and the distance of home-agricultural technology station. This study aims to provide empirical evidence for the formulation of strategies and plans to promote sustainable agricultural development.